2021
DOI: 10.23960/jsl19161-178
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Karakteristik Kimia terhadap Sifat Mekanis dan Keawetan Alami Tiga Jenis Kayu Kurang Digunakan (Effect of Chemical Characteristics on Mechanical and Natural Durability Properties of Three Lesser-Used Wood Species)

Abstract: Chemical, mechanical, and natural durability properties of three lesser-used wood species from North Kalimantan, namely nyatoh (Palaquium lanceolatum), pisang putih (Mezzettia leptopoda), and sepetir (Sindora wallichii) woods,were analyzed to seek the interrelationships amongthem and give an overview related to their utilization. The results showed that pH values of three wood species were categorized into moderate to weak acid levels. The extractive contentsin hot and cold water as well as in NaOH 1% of sepet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…MOE is an important parameter, specifically for timber construction. According to Augustina et al (2021), a high wood density in the wood indicated a high -cellulose content, thereby producing high MOE and MOR values. Knapic et al ( 2022) stated that wood density plays an important role in determining strength and has a stronger relationship with MOR than with MOE.…”
Section: Mechanical Properties Of Simalambuo Wood Modulus Of Elastici...mentioning
confidence: 99%
See 1 more Smart Citation
“…MOE is an important parameter, specifically for timber construction. According to Augustina et al (2021), a high wood density in the wood indicated a high -cellulose content, thereby producing high MOE and MOR values. Knapic et al ( 2022) stated that wood density plays an important role in determining strength and has a stronger relationship with MOR than with MOE.…”
Section: Mechanical Properties Of Simalambuo Wood Modulus Of Elastici...mentioning
confidence: 99%
“…Furthermore, -cellulose is cellulose with a polymerization degree of 600-15,000 and materials with high content indicated high-quality raw materials. Augustina et al (2021) stated that a narrower vessel diameter shows a portion of the cell wall, and the amount of cellulose is greater. The density is higher, causing the wood to be denser by producing strength.…”
Section: Holocellulose -Cellulose and Hemicellulosementioning
confidence: 99%